Edukasi Anti Bullying di SDN Dipatiukur Kecamatan Pusakajaya Kabupaten Subang - Ferdy Samuel Sagala; Yayang Tia Sri Rahayu; Yuli Maisaroh Sarumpaet; Pepep Sudarna; Adam Hidayat Pamungkas; Ucika Nurinna (Jurnal Kolaborasi Pengabdian Masyarakat Fakultas Ilmu Administrasi, 2025)
Abstract Bullying is a prevalent social issue in elementary school environments, manifesting in physical, verbal, and nonverbal forms. This condition negatively affects students’ psychological, social, and academic development. The Student Community Service Program (KKNM) of Universitas Subang, Group 26, conducted an Anti-Bullying education initiative at SDN Dipatiukur, Bojongjaya Village, Pusakajaya District, Subang Regency, targeting 5th and 6th grade students. The activity was carried out using a participatory-educational approach through the following stages: (1) presentation of objectives, (2) initial discussion, (3) pre-test, (4) ice breaking, (5) delivery of material on bullying, its types, impacts, and coping strategies, (6) Q&A session, (7) screening of an educational film, (8) post-test, and (9) closing and creation of educational content.The results showed a significant increase in students’ understanding of the concept of bullying and how to deal with it. The pre-test revealed that only 40% of students had a correct understanding of bullying, while the post-test showed an increase to 87%. Additionally, students became more open in sharing their experiences and showed greater empathy toward their peers. This program demonstrates the importance of early anti-bullying education in creating a safe and comfortable school environment. Keywords: KKNM, Anti-Bullying, Character Education, SDN Dipatiukur, Elementary School Student   Abstrak Bullying merupakan salah satu permasalahan sosial yang marak terjadi di lingkungan sekolah dasar, baik dalam bentuk fisik, verbal, maupun nonverbal. Kondisi ini berdampak negatif terhadap perkembangan psikologis, sosial, dan akademik siswa. Program Kuliah Kerja Nyata Mahasiswa (KKNM) Universitas Subang Kelompok 26 melaksanakan kegiatan edukasi Anti Bullying di SDN Dipatiukur Desa Bojongjaya, Kecamatan Pusakajaya, Kabupaten Subang, dengan sasaran siswa kelas 5 dan 6. Kegiatan dilakukan melalui pendekatan partisipatif-edukatif dengan tahapan: (1) penyampaian tujuan, (2) diskusi awal, (3) pre-test, (4) ice breaking, (5) pemaparan materi tentang bullying, jenis, dampak, dan cara menghadapi, (6) sesi tanya jawab, (7) menonton film edukatif, (8) post-test, dan (9) penutupan serta pembuatan konten edukasi. Hasil kegiatan menunjukkan peningkatan pemahaman siswa tentang konsep bullying dan cara menghadapinya. Pre-test memperlihatkan hanya 40% siswa memahami bullying secara benar, sedangkan setelah post-test, tingkat pemahaman meningkat menjadi 87%. Selain itu, siswa menunjukkan sikap lebih terbuka dalam menyampaikan pengalaman, serta lebih peduli terhadap teman sebayanya. Program ini membuktikan pentingnya edukasi dini tentang anti bullying dalam menciptakan lingkungan sekolah yang aman dan nyaman. Kata Kunci: KKNM, Anti Bullying, Pendidikan Karakter, SDN Dipatiukur, Siswa Sekolah Dasar